Parerga to the Stadiasmus Patarensis (9): the Question of Kaunos and Lycia - Sencer Şahin (Gephyra, 2013)
An erroneous interpretation of route 12, 24 and 46 of SP, which indicate as terminal points of the Lycian road system the nearest, most important boundary cities (Kaunos, Kibyra and Attaleia) on interregional crossroads in the neighbouring provinces of Asia and Galatia, has led recent scholarship to draw wrong conclusions. It is argued that the Carian city of Kaunos, which formerly belonged to the province of Asia, had already been integrated into the newly founded single province of Lycia as early as in 43 CE. However, the material adduced to support this assumption is more apt to rule it out, and this article presents further reasons why this is so. It will be shown that Kaunos as well as Attaleia and Kibyra are to be understood as having been outside Lycia when it was set up as a single province. Only when the double province Lycia et Pamphylia was created by Vespasian in about 70 CE were this city, certainly with its territory, and Pamphylia as well as parts of Pisidia added to the new province.